Structural investigations of the polysaccharide gum exudates from Brabeiurn Stellatifoliurn and Grevillea Robusta - Van der Bijl, Pieter (Department of Chemistry, 2023)
The structures of the polysaccharide gum exudates from Brabeium stellatifolium and Grevillea robusta, both belonging to the family Proteaceae, have been investigated and compared. A general similarity between these two polysaccharide gums, both of high molecular weight, was apparent, although techniques such as methylation analysis, Smith-degradation and partial acid hydrolysis revealed small differences in fine structure. Brabeium stellatifolium gum was examined in somewhat more detail. In a study of hydrolysis of the gum by acid the degradation process was followed by gel chromatography. The elution curves obtained at different stages of hydrolysis demonstrated the production of fragments of preferred molecular size, and permitted analysis of the degradation pattern in terms of the fission of peripheral and of internal linkages. Hydrolysis of methylated Brabeium stellatifolium g·um, followed by separation of the resulting methyl ethers on a cellulose column, gave results in good agreement with those obtained on semi-quantitative GLC analysis of the methanolysate of the methylated gum. In Smith-degradation studies of both Brabeium stellatifolium and Grevillea robusta gums the conditions generally used for mild acid hydrolysis of the reduced, oxidised polysaccharides were modified to ensure complete cleavage of acetal linkages. Both gums yielded Smithdegradation products exhibiting a high degree of polyrnolecularity. The relative decreases in weight - average molecular weight M w, accompanying successive Smith-¬ degradations were similar for the two gums, A further point of resemblance was the unusual resistance to periodate oxidation of D-mannose and uronic acid residues in both gums.